2015
DOI: 10.1155/2016/1492694
|View full text |Cite
|
Sign up to set email alerts
|

TGF‐β1 Induces the Dual Regulation of Hepatic Progenitor Cells with Both Anti‐ and Proliver Fibrosis

Abstract: Transforming growth factor-beta 1 (TGF-β1) plays a central role in hepatic progenitor cells- (HPCs-) mediated liver repair and fibrosis. However, different effects of TGF-β1 on progenitor cells have not been described. In this study, both in vitro (HPCs cocultured with hepatic stellate cells (HSCs) in transwells) and in vivo (CCl4-injured liver fibrosis rat) systems were used to evaluate the impacts. We found that HPCs pretreated with TGF-β1 for 12 hours inhibited the activation of HSCs, while sensitization fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 29 publications
0
24
0
1
Order By: Relevance
“…A similar scenario may occur in terms of platelets regulating fibrosis vs liver regeneration, by releasing factors that cause fibrosis, such as TGF-b1, or factors that mobilize and promote proliferation of stem cells and progenitor cells during regeneration, such as serotonin or stromal-cell derived factor-1. A recent study reported that reprogramming myofibroblasts and stimulating stem cells differentially regulates liver fibrosis and regeneration in a manner dependent on transcriptional expression and the duration of TGF-b1 stimulation, 54,55 thus supporting the dual-role concept of platelets, which might 478 GHAFOORY et al 13 MARCH 2018 x VOLUME 2, NUMBER 5…”
Section: Pf4cretgfb1mentioning
confidence: 93%
“…A similar scenario may occur in terms of platelets regulating fibrosis vs liver regeneration, by releasing factors that cause fibrosis, such as TGF-b1, or factors that mobilize and promote proliferation of stem cells and progenitor cells during regeneration, such as serotonin or stromal-cell derived factor-1. A recent study reported that reprogramming myofibroblasts and stimulating stem cells differentially regulates liver fibrosis and regeneration in a manner dependent on transcriptional expression and the duration of TGF-b1 stimulation, 54,55 thus supporting the dual-role concept of platelets, which might 478 GHAFOORY et al 13 MARCH 2018 x VOLUME 2, NUMBER 5…”
Section: Pf4cretgfb1mentioning
confidence: 93%
“…However, initial enthusiasm for using bone marrow to heal the heart has been tempered with disappointment, as stem cells from this noncardiac tissue have not shown a sufficient native potential to generate myocardial tissue [ 9 , 10 , 12 ]. Recently, we reported that exposure of bone marrow stem cells to the G9a histone methyltransferase (HMTase) inhibitor BIX01294 can enhance their cardiac competency [ 13 , 14 ]. Bone marrow mesenchymal stem cells (MSCs) treated with BIX01294 showed an induced expression of Mesp1 and brachyury [ 13 , 14 ], which are markers associated with precardiac progenitors in the early embryo [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported that exposure of bone marrow stem cells to the G9a histone methyltransferase (HMTase) inhibitor BIX01294 can enhance their cardiac competency [ 13 , 14 ]. Bone marrow mesenchymal stem cells (MSCs) treated with BIX01294 showed an induced expression of Mesp1 and brachyury [ 13 , 14 ], which are markers associated with precardiac progenitors in the early embryo [ 15 17 ]. Moreover, BIX01294 treatment subsequently allowed MSCs to undergo myocardial differentiation in response to Wnt11 [ 13 , 14 ], which is a primary extracellular factor that initiates cardiogenesis during early development [ 18 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations